Pyrodinium bahamense and other dinoflagellate cyst distribution in surface sediments of Irong-Irong Bay, Catbalogan City, Western Samar, Philippines - Zabala, Kevin T.; Tan, Irene L. (2017)
The present study aimed to provide a baseline assessment of the abundance, distribution, and density of dinoflagellate cysts in the surface sediments of the recently reported HAB-positive Irong-Irong Bay in Catbalogan City, Western Samar. More importantly, it identified toxic dinoflagellate cyst species such as Pyrodinium bahamense that may have contributed to the red tide outbreaks in the area. Sediment samples were collected from 11 stations using a grab sampler on January 2017. Dinoflagellate cysts were isolated from surface sediments through palynological technique. They were viewed using an inverted microscope and identified to the lowest possible taxonomic level. Cyst densities were calculated and expressed as cysts per gram of dry weight (cysts g raise to negative 1 DW). A total of 19 cyst species were identified from all stations, belonging to three orders: Gonyaulacales, Gymnodiniales, and Peridiniales. Cyst density ranged from 2-10 cysts g raise to negative 1 DW. P. bahamense cyst concentration determined was 7 cysts g raise to negative 1 DW. The surface sediments of the bay was mostly classified as sandy mud, with only three stations having sandy substrates. Other physicochemical characteristics of the surface sediments and overlying waters such as depth, dry bulk density, and nutrient content may have also affected cyst concentration in the study area.